2006
DOI: 10.1101/gad.1439206
|View full text |Cite
|
Sign up to set email alerts
|

SAS-mediated acetylation of histone H4 Lys 16 is required for H2A.Z incorporation at subtelomeric regions in Saccharomyces cerevisiae

Abstract: The yeast SAS (Something About Silencing) complex and the histone variant H2A.Z have both previously been linked to an antisilencing function at the subtelomeric regions. SAS is an H4 Lys 16-specific histone acetyltransferase complex. Here we demonstrate that the H4 Lys 16 acetylation by SAS is required for efficient H2A.Z incorporation near telomeres. The presence of H4 Lys 16 acetylation and H2A.Z synergistically prevent the ectopic propagation of heterochromatin. Overall, our data suggest a novel antisilenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 39 publications
7
92
0
2
Order By: Relevance
“…With respect to histone variants, studies in yeast have shown that H4K16 acetylation is a prerequisite to the incorporation of Htz1 Shia et al, 2006), the counterpart of the mammalian H2A.Z, an H2A variant involved in transcription activation and implicated in maintaining the boundaries of heterochromatin in yeast. Also, deacetylation of K16 is directly linked to histone H1 isoform H1.4 recruitment in mammalian cells upon silencing (Vaquero et al, 2004).…”
Section: Histone H4 Lysine 16 Interplaysmentioning
confidence: 99%
“…With respect to histone variants, studies in yeast have shown that H4K16 acetylation is a prerequisite to the incorporation of Htz1 Shia et al, 2006), the counterpart of the mammalian H2A.Z, an H2A variant involved in transcription activation and implicated in maintaining the boundaries of heterochromatin in yeast. Also, deacetylation of K16 is directly linked to histone H1 isoform H1.4 recruitment in mammalian cells upon silencing (Vaquero et al, 2004).…”
Section: Histone H4 Lysine 16 Interplaysmentioning
confidence: 99%
“…However, Sas2's telomeric silencing function stems from its role as a boundary factor in preventing the spreading of heterochromatin into euchromatic regions (Kimura et al, 2002;Suka et al, 2002), rather than from direct promoter acetylation. In addition, the boundary function of Sas2 may entail the deposition of H2A.Z in subtelomeric regions (Shia et al, 2006). Therefore, by analogy, dTip60 may also act in gene repression in flies as a boundary factor by restricting heterochromatin to its designated genomic region.…”
Section: Dtip60 Might Mediate Its Repressive Function By Deposition Omentioning
confidence: 99%
“…SAS-I globally acetylates H4 K16 in subtelomeric regions (17). Similarly, the HDAC Rpd3 provides global chromatin deacetylation in addition to its function in local gene repression (18).…”
mentioning
confidence: 99%